Mitigation of landslides due to land use in population settlements - Kusmana, Dody; Paikun; Rohadi, Edi (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2021)
The implementation of housing development carried out by the developer is suspected of not meeting the administrative, technical and environmental requirements. By not carrying out the provisions to carry out efforts to stabilize slopes and apply appropriate drainage systems, to minimize loading on the slopes and allegedly not conducting geological studies of environmental planning or basic engineering geology as the basis for the implementation of development so that the impact on the environment in the form of the Cimanggung landslide occurs.Landslide is one of the natural disasters that often hit hilly areas in the wet tropics. Mass movement, generally caused by gravitational forces and sometimes vibrations or earthquakes also support the occurrence. Mass movement in the form of landslides occurs due to the shear debris along the landslide area which is the limit of the movement of the soil or rock mass. Soil motion is the process of moving a mass of rock/soil due to the force of gravity. Soil motion is often referred to as a landslide of the soil/rock mass and is generally defined as a movement of soil and/or rock from its place of origin due to the influence of gravity.